The evolution of interfacial intermetallic compound growth and solder joint strength of Sn-40Pb/Cu under thermal aging / Ramani Mayappan - Mayappan, Ramani (Penerbit UiTM (UiTM Press), 2024)
A solder joint serves as a mechanical support and heat dissipator in an electronics board. Thus, logically, there is a need for high reliability. The reliability of solder joints in electronic systems is an issue that affects all aspects of the production and use stages. In any aspect of packaging technology, the reliability of solder joints plays an important role in determining the lifetime of electronic devices. In this study, the intermetallic formation and solder joint strength of a conventional Sn-Pb solder were investigated. The solder joints were prepared at 250 oC with a soldering time of 1 min. The solder joints were aged at various temperatures and times. Aging was performed at 50, 100 and 150 oC for 100, 250 and 500 h. For intermetallic observation, the solder joint was cross-sectioned and mounted in epoxy resin. After polishing, the surface was observed using a Scanning Electron Microscope (SEM) for intermetallic study. The joint strength was measured using an Instron machine and the fracture surface was observed using a SEM. For a low aging temperature and duration, a Cu6Sn5 intermetallic compound was formed with a scalloped morphology. This intermetallic structure was transformed into a flat structure at higher aging temperatures and durations. As aging progressed, another thin and flat intermetallic layer formed near the Cu interface. The intermetallic compound was identified as Cu3Sn. The solder joint strength degraded at a later stage of aging owing to the excessive growth of the intermetallic.